Task-oriented reading in higher education: effects of two types of scripted collaboration - Okkinga, Mariska; van Gelderen, Amos (Frontiers in Education, 2025)
IntroductionTask-oriented reading is an important skill in higher education. However, many students in higher education have little experience in this type of reading and lack strategies for executing it efficiently and effectively. The aim of the present study is to design and test a learning environment in realistic classroom settings to foster task-oriented reading in higher education.MethodsA learning environment was designed and tested experimentally in a series of lessons to aid teacher students of different disciplines (N = 105) in the process of task-oriented reading in two stages: homework and group discussion. Using a pre-post experimental design, two types of scripted collaboration were compared: one group received role assignment only, while the other group additionally received instructions about different phases in the collaboration process. Two task-oriented reading tasks (pre- and post-test) were designed, each consisting of four texts and 11 open-ended questions about these texts. Students’ activities during task execution were logged.ResultsBoth groups significantly improved performance between pre- and posttest. However, results showed no significant differences between the two groups in growth between pre- and posttest. Logs of task execution showed that all students spent more time on reading relevant text parts at posttest and spent less time on question reading and answering at posttest, suggesting that students executed task-oriented reading more efficiently as a result of the learning environment.DiscussionThe results suggest that students exhibited greater efficiency in navigating between their task and text representation, which is in accordance with literature on the process of task-oriented reading. No significant differences were found between the two types of scripting, indicating that the phased discussion did not confer any advantage over role assignment only. This difference may be attributed to the relatively small difference between the two types of scripting.